Osteometry and migration(s) of reindeer (Rangifer tarandus) in South-West France during the Last Pleniglacial and the Last Glacial (21 500- 13 000 cal. BP) - Kuntz, Delphine (HAL CCSD, 2011)
This doctoral research aims at characterizing morphological fluctuations resulting from climate change in palaeolithic reindeers from Southwest France. Indeed, the Last Pleniglacial and the Last Glacial (between 21 500 - 13 000 cal. BP) constituted periods of particularly strong palaeoclimatic and palaeoenvironmental constraints, which ended, either directly or indirectly, in repercussions on the body size of reindeer populations. The series analyzed within the framework of this work result from both current and fossil registers. Several samples of current populations (Norway, Finland, and Greenland) were thus analyzed, in order to experiment the methodology and envisage morphological comparisons with the past populations. The palaeolithic corpus is composed of 29 natural and anthropological assemblages of Southwest France, dated mainly from the Last Pleniglacial and the Last Glacial. Since the Variability Size Index method recently applied to palaeolithic reindeer raises issues, particularly relating to the determination of an assemblage's sex-ratio, to the characterization or not of observed morphological differences -either isometric and allometric-, we decided to use a new methodology combining several statistical tools applied to a new size index (VSI*: modified Variability Size Index). Osteometric and statistical analyses that we performed tend to identify temporal morphological fluctuations, demonstrating adaptations of the specie. From a synchronic standpoint, the results allow to reject the hypothesis previously asserted regarding differences between Last Glacial reindeers from Landes on the one hand and the Dordogne/Gironde sector, on the other hand. Seasonal data however tend to indicate an absence of large-scale migrations of reindeers according to such a North/South axis. Nonetheless, the existence of different populations between reindeers of Landes and those of the Aude basin is proposed. Hence, Southwest France, at the end of the upper Palaeolithic, would have been occupied continuously by ...